Interference microscopy highlights properties and peculiarities of SAPO STA-7 crystals - Tzoulaki, Despina; Castro, Maria J.; Kärger, Jörg; Wright, Paul Anthony (Diffusion Fundamentals, 2007)
In the framework of this study a new generation of SAPO STA-7 crystals has been investigated with the help of Interference Microscopy. The ability of the abovementioned technique to record intracrystalline concentration profiles during uptake/release of guest molecules revealed oddities of the system under study. In other words, these crystals have the tendency to break in the middle, enhancing in this way diffusion. On the other hand, molecules have to confront high surface barriers when they try to diffuse through the other sides of the crystal, where it is not broken.